Policy reforms in Indonesia a political economy perspective - Wahid, Abu N. M. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1996)
During the 1970s the Indonesian economy grew at a rapid rate. This growth was primarily attributable to the government's oil revenue and massive expansion of public sector in Indonesia. However, the decline in oil price of the 1980s adversely affected the growth and stability of the economy. The government clearly recognized the fact that a restructuring of the economy was imperative. The present paper is a critical analysis of this restructuring effort. The paper argues that the restructuring was initiated with a view to enabling the private sector and non-oil exports to play a greater role in the expansion of employment and income. The reform program began in 1983 with political and ethnic diversity and economic agenda. The political agenda includes the issues of Pribumism and ethnic diversity and economic nationalism while the economic agenda addressed the privatization initiative, fiscal/monetary policies and trade/investment policies. The reform process that was initiated by the government was partially successful. This paper argues that the main reason for the reform not being fully successful is the corruption of the bureaucracy and too much political orientation of the policies.